2021
DOI: 10.1080/21655979.2021.1926200
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence and risk factors of acute kidney injury in patients undergoing hip fracture surgery: a meta-analysis

Abstract: Acute kidney injury (AKI) was a frequent complication following hip fracture surgery, but recent studies reported inconsistent findings. Our study was aimed at clarifying the prevalence and risk factors of AKI after hip fracture surgery. Pubmed, Embase, and Web of Science were systematically searched from the inception to March 2020 to identify observational studies investigating the prevalence and risk factors of AKI in patients undergoing hip fracture surgery. Pooled prevalence and odds ratios (ORs) with 95%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 31 publications
1
4
1
Order By: Relevance
“… 25 Moreover, a recent meta-analysis consisting of 11 studies with 16,421 surgical hip fracture patients found the pooled prevalence of AKI was 17% (95% CI 14–21%). 28 Compared with those studies, the incidence of AKI in the current study was much higher (48.2%) and might at least partly explained by differences in patient populations and severity of disease. Furthermore, rib fracture patients especially in ICU occasionally require surgical treatment and commonly complain about chest pain, atelectasis, hypoventilation, hypoxemia, respiratory failure and subsequent cardiac complications.…”
Section: Discussioncontrasting
confidence: 84%
“… 25 Moreover, a recent meta-analysis consisting of 11 studies with 16,421 surgical hip fracture patients found the pooled prevalence of AKI was 17% (95% CI 14–21%). 28 Compared with those studies, the incidence of AKI in the current study was much higher (48.2%) and might at least partly explained by differences in patient populations and severity of disease. Furthermore, rib fracture patients especially in ICU occasionally require surgical treatment and commonly complain about chest pain, atelectasis, hypoventilation, hypoxemia, respiratory failure and subsequent cardiac complications.…”
Section: Discussioncontrasting
confidence: 84%
“…Previous studies proposed that risk factors such as age, gender, BMI, preexisting CKD, pre-and postoperative hypoalbuminemia, comorbidities, hemoglobin changes, blood loss, and other factors were independent risk factors for AKI, 9,[13][14][15][16] although some other studies identified different risk factors. 11,12 Chen et al studied patients following orthopedic surgery and proposed that age, hypertension, DM, hypoproteinemia, receipt of transfusion, and duration of low mean arterial pressure were independent risk factors for AKI. 17 We analyzed the and many other factors, and our multivariate logistic regression results indicated that advanced age, high ASA score, preexisting CKD, receipt of cemented surgery, and large decrease of hemoglobin on the first day after surgery were significant and independent risk factors for AKI.…”
Section: Discussionmentioning
confidence: 99%
“…10 Many risk factors of AKI after hip fracture surgery had been identified in literature. [7][8][9]11 There have also been efforts to develop interventions for the prevention and treatment of AKI after hip fracture surgery based on these reported risk factors. However, rare predictive model for AKI after hip fracture surgery is currently available.…”
Section: Introductionmentioning
confidence: 99%
“…A large-scale cohort study estimated the incidence of AKI for postoperative T&O patients at 10.8% 6. Studies focusing on AKI following elective procedures found rates of 6.8%5 and 8.2%1 compared with 17% of patients following emergency surgery 3 7. Importantly, while undergoing an operation is in itself a risk factor for developing an AKI, emergency T&O patients in particular are often at greater risk, given their frailty and comorbidities 3…”
Section: Problemmentioning
confidence: 99%